2019
DOI: 10.15244/pjoes/99100
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Functional Diversity Responses to Different Revegetation Types in Baishilazi Nature Reserve

Abstract: Soil microorganisms play important roles in the dynamic regulation of organic matter in the forest ecosystem and are affected by different revegetation types. To reveal the influence of different revegetation types on soil microorganisms, we examined soil properties, soil microbial activity and diversity in Baishilazi Nature Reserve, including two planted coniferous forests (LG: Larix gmelinii, PK: Pinus koraiensis), two natural secondary broadleaf forests (JM: Juglans mandshurica, QM: Quercus mongolica), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
4
3
2
Order By: Relevance
“…The organic carbon and total nitrogen contents were positively correlated with the Shannon index in our data, and soil C/N was negatively correlated with the same index. These results are inconsistent with what was reported by Deng et al (2019). Different vegetation types produce different amounts and qualities of plant litter input (Ushio et al 2010a(Ushio et al , 2010bZhang et al 2006), promoting different types of microorganisms in the soil (Sariyildiz and Anderson 2003;Tripathi et al 2013).…”
Section: Different Vegetation Types Contribute To Different Soil Microbial Functional Diversitiescontrasting
confidence: 74%
“…The organic carbon and total nitrogen contents were positively correlated with the Shannon index in our data, and soil C/N was negatively correlated with the same index. These results are inconsistent with what was reported by Deng et al (2019). Different vegetation types produce different amounts and qualities of plant litter input (Ushio et al 2010a(Ushio et al , 2010bZhang et al 2006), promoting different types of microorganisms in the soil (Sariyildiz and Anderson 2003;Tripathi et al 2013).…”
Section: Different Vegetation Types Contribute To Different Soil Microbial Functional Diversitiescontrasting
confidence: 74%
“…Also, significant differences in the concentrations of soil TC, TN, C/N, AN, TP, AP, and AK differed significantly among PKSZ, RPL, and PSC (Table 1 ), which were highly similar to those reported by Xu et al ( 2014 ). What’s more, compared to PKSZ and PSC, RPL could better improve soil TC, TN, TP, and AP (Table 1 ), which was consistent with previous studies demonstrated that broadleaf forest could improve soil nutrients than coniferous forest (Deng et al 2019a , b ). As we all know, the turnover of litter and fine roots is the main way of soil organic matter input, and the content of organic matter can affect the process of nitrogen transformation and accumulation.…”
Section: Discussionsupporting
confidence: 89%
“…Also, signi cant differences in the concentrations of soil TC, TN, C/N, AN, TP, AP, and AK differed signi cantly among PKSZ, RPL, and PSC (Table 1), which were highly similar to those reported by (hang et al ( 2014). What's more, compared to PKSZ and PSC, RPL could better improve soil TC, TN, TP, and AP (Table 1), which was consistent with previous studies demonstrated that broadleaf forest could improve soil nutrients than coniferous forest (Deng et al, 2019a;Deng et al, 2019b). As we all know, the turnover of litter and ne roots is the main way of soil organic matter input, and the content of organic matter can affect the process of nitrogen transformation and accumulation.…”
Section: Discussionsupporting
confidence: 88%